2019
DOI: 10.14507/epaa.27.4460
|View full text |Cite
|
Sign up to set email alerts
|

State-wide implementation of edTPA in preparation for high-stakes testing: A mixed-methods study of the concerns of edTPA coordinators

Abstract: This study examined the implementation of high-stakes adoption of edTPA® in one state in the year prior to consequential use of edTPA scores for teacher licensure. Using a mixed methods design, we investigated concerns of coordinators who were responsible for edTPA implementation in their institutions. We utilized the Concerns Based Adoption Model (CBAM) to understand edTPA coordinators’ Stages of Concern, the nature of the challenges they faced, and the professional development opportunities that alleviated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…As fewer educators became involved, teacher educators left with the responsibility realized that the program had fewer experts to share the workload. Researchers have noted similar responses and reactions from teacher educators to a mandate, noting their compliance rather than inquiry (Kornfeld et al, 2007) and considered educators' stages of concern, recognizing consequences for candidates, themselves, and their program (Many et al, 2019;Qian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As fewer educators became involved, teacher educators left with the responsibility realized that the program had fewer experts to share the workload. Researchers have noted similar responses and reactions from teacher educators to a mandate, noting their compliance rather than inquiry (Kornfeld et al, 2007) and considered educators' stages of concern, recognizing consequences for candidates, themselves, and their program (Many et al, 2019;Qian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that administrators face challenges motivating teacher educators to engage in, rather than to resist, new policy mandates (Peck et al, 2010;Sloan, 2013). By recognizing educators' stages of concern, in response to policy mandates, teacher preparation program leaders can learn how to engage faculty in professional development (Many et al, 2019;Qian, Fayne, & Lieman, 2017). Some educational scholars contend that leaders in higher education must come to understand how they are influenced by policy mandates and the conditions for developing an inquiry stance to learn and change (Dewey, 1938, Peck et al, 2010Peck & McDonald, 2013;Whittaker & Nelson, 2013).…”
Section: Literature Related To Teacher Performance Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the outsourcing of scoring to external evaluators has been found to erode the pedagogic relationships faculty and university supervisors develop with teacher candidates. Faculty may resort to “teaching to the test” as a means to bolster student edTPA pass rates, which can counter their pedagogical and philosophical beliefs with regard to preparing students for the academic, professional, and socio-emotional aspects of the profession (Donovan & Cannon, 2018; Many et al, 2019; Sato, 2014; Consequently, teacher candidates may be deprived from receiving individualized feedback on portfolios that can aid in their development into reflective and culturally-responsive educators. Moreover, COE faculty risk losing autonomy over their curriculum and instruction if education degree programs and coursework are aligned with corporate interests versus the needs of students and communities where aspiring teachers will work.…”
Section: Literature Reviewmentioning
confidence: 99%